2018
DOI: 10.14716/ijtech.v9i5.2106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spatial Layout in Health Care Waiting Areas based on Simulation of Droplet Movement Trace

Abstract: This paper addresses the issue of airborne transmission of diseases in relation to spatial layout in health care facilities. In particular, this study analyzes the occurrence of airborne transmission in the waiting areas of puskesmas, a form of primary health care facilities that are distributed in many cities and villages in Indonesia. The study uses computational fluid dynamics (CFD) analysis as a design tool to examine the potential for airborne infection by analyzing the simulated droplet movement in a wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 14 publications
0
10
0
6
Order By: Relevance
“…In particular, this study attempts to analyze the role of the two operations types, the tours and the maps, within a sequence of a wayfinding journey in a hospital building. Some studies in hospital and healthcare facilities have revealed the role of spatial configuration in hospital performance (Johanes & Atmodiwirjo, 2015;Sengke et al, 2020;Yatmo et al, 2018Yatmo et al, , 2021, including issues with wayfinding (Pati et al, 2015;Carpman et al, 2016;Johanes & Yatmo, 2018). This current study demonstrates how the movement of visitors can take place in a particular spatial configuration of a hospital.…”
Section: Introductionmentioning
confidence: 51%
“…In particular, this study attempts to analyze the role of the two operations types, the tours and the maps, within a sequence of a wayfinding journey in a hospital building. Some studies in hospital and healthcare facilities have revealed the role of spatial configuration in hospital performance (Johanes & Atmodiwirjo, 2015;Sengke et al, 2020;Yatmo et al, 2018Yatmo et al, , 2021, including issues with wayfinding (Pati et al, 2015;Carpman et al, 2016;Johanes & Yatmo, 2018). This current study demonstrates how the movement of visitors can take place in a particular spatial configuration of a hospital.…”
Section: Introductionmentioning
confidence: 51%
“…It is crucial to maintain air pressure (positive, negative, or alternating pressure) and air flow, as well as providing an anteroom and ventilation, either naturally, mechanically, or through hybrid measures (Atkinson et al, 2009;Yuen et al, 2012). Controlling the air pressure and air change rate would help the control of airflow within the room, hence reducing possible airborne infection (Yatmo et al, 2018). Notably, natural ventilation is the least costly, hybrid ventilation is the most suitable for variable weather conditions, and mechanical ventilation is the easiest way to achieve the desired air circulation standard despite also being the most expensive (Atkinson et al, 2009).…”
Section: Design Criteria For Isolation Facilitiesmentioning
confidence: 99%
“…The first important principle of layers' adaptation is that each layer does not adapt solely on its own but might interact or combine with another layer. For example, studies have demonstrated that the sanitary and ventilation systems are significant in distributing potentially contaminated droplets through the water and airflow of a dwelling (Banham, 1984;Yatmo et al, 2018). However, a dwelling's spatial layout also directs the potentially contaminated airflow .…”
Section: Layers' Adaptation and Connections During A Pandemicmentioning
confidence: 99%